2022
DOI: 10.1371/journal.pgen.1010243
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the history of founder events using genome-wide patterns of allele sharing across individuals

Abstract: Founder events play a critical role in shaping genetic diversity, fitness and disease risk in a population. Yet our understanding of the prevalence and distribution of founder events in humans and other species remains incomplete, as most existing methods require large sample sizes or phased genomes. Thus, we developed ASCEND that measures the correlation in allele sharing between pairs of individuals across the genome to infer the age and strength of founder events. We show that ASCEND can reliably estimate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 81 publications
(117 reference statements)
2
27
0
Order By: Relevance
“…The use of whole genome data also enables the measurement of lengths of long tracts of homozygous genotypes or runs of homozygosity (RoH) segments (Ceballos, et al 2018). A number of previous studies showed that bottleneck and founder effects increase the number of long RoHs (Bortoluzzi, et al 2020; Khan, et al 2021; Sánchez-Barreiro F 2021; Tournebize, et al 2022). Hence, estimating the lengths of RoH in dingoes and comparing them with those observed for other canines will potentially reveal whether the size of the founding dingo population was small.…”
Section: Introductionmentioning
confidence: 99%
“…The use of whole genome data also enables the measurement of lengths of long tracts of homozygous genotypes or runs of homozygosity (RoH) segments (Ceballos, et al 2018). A number of previous studies showed that bottleneck and founder effects increase the number of long RoHs (Bortoluzzi, et al 2020; Khan, et al 2021; Sánchez-Barreiro F 2021; Tournebize, et al 2022). Hence, estimating the lengths of RoH in dingoes and comparing them with those observed for other canines will potentially reveal whether the size of the founding dingo population was small.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature from historical 3 , clinical 1 , 10 14 , and population genetic studies 4 suggests evidence of a population bottleneck in the European settlement of NL. Furthermore, recent work has shown that island communities tend to experience stronger founder effects 40 . Therefore, we set out to characterise the magnitude of the NL founder effect using the NL 1,807 dataset and comparing this with European source populations.…”
Section: Resultsmentioning
confidence: 99%
“…S3A) was built assuming a standstill in Beringia at 26,000 yr B.P., the settlement of America at 15,000 yr B.P., and divergence between Central and South American populations at 13,000 yr B.P. The effective population size and its changes over time were based on the Castro e Silva et al ( 60 ) dataset inferred through ASCEND ( 61 ) and IBDNe ( 62 ) softwares. We assume a mutation rate of 1 × 10 −8 and a generation time of 25 years.…”
Section: Methodsmentioning
confidence: 99%